What does the public think about microplastics? Insights from an empirical analysis of mental models elicited through free associations - Felipe-Rodriguez, Marcos; Böhm, Gisela; Doran, Rouven (Frontiers in Psychology, 2022)
A survey was distributed among a representative sample of the adult Norwegian population to explore the public understanding of microplastics and assess its associations with sociodemographic characteristics and personal value orientations. For this purpose, respondents were asked to report the first thing that came to mind when they read or heard the word “microplastics”. Results indicate that the public seem to think of microplastics as something bad that might pollute the ocean and harm animal species. Awareness of the sources of microplastics appeared to be rather low, and few respondents mentioned potential ways to solve the problem. Responses differed based on certain socio-demographic characteristics; for instance, female and younger respondents were more likely to think about the spread and causes/sources of microplastics, whereas a higher educational level was associated positively with thinking of ways to solve the problem. Additional analyses indicated further relationships between personal values and free associations with microplastics. Endorsing self-transcendence and openness-to-change was associated with thinking of ways to solve and consequences of microplastics. Endorsing openness-to-change was also related to thinking of causes/sources of microplastics. These findings may provide valuable insights for decision-makers who are involved in the development and design of communication strategies and interventions to reduce plastic waste, and those attempting to understand public perceptions of the risks and benefits of the global environmental issue of microplastics.